Flexing as a Strategy to Garner Popularity on Instagram - Vivi Alaida Najihatul Fadliyah,; Iqbal Hussain Alamyar,; Deyisnil Fariadi, (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2025)
Flexing, or showing off wealth and luxury, has become a widespread phenomenon on social media, especially among celebrities and influencers. This behavior is used to attract attention, increase popularity, and strengthen one's image in front of an audience. Flexing often utilizes a luxurious lifestyle as a personal marketing strategy. This study uses media text analysis with a Critical Discourse Analysis (CDA) approach developed by Norman Fairclough. Data was collected through direct observation of content uploaded to the Instagram account @siscakohl. The results show that @siscakohl effectively uses flexing strategies to gain popularity. Content that displays a luxurious lifestyle and extravagance successfully attracts the attention of many followers, increases interaction, and strengthens her personal image as a successful influencer. Flexing is also used to build narratives of success and aspiration, which are relevant to the audience's desire to achieve higher social and economic status. The contribution of this research lies in a new understanding of self-branding practices through flexing culture on social media, which not only functions as a form of personal expression but also as a communication strategy that influences the construction of identity and social relations in the digital space. These findings can be a reference for further research in the study of digital communication, popular culture, and new media.